PENGARUH METODE EKSPERIMEN TERHADAP KETERAMPILAN PROSES SAINS PADA ANAK USIA 5 – 6 TAHUN DI TK ADINDA - Leni Maryani; Dwi Suryani , Yuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the experimental method on science process skills in children aged 5-6 years at Adinda Kindergarten. The research method used in this study is a quantitative pre-experimental approach with a one-group pretest-posttest design. Data collection techniques used action tests, observation, and documentation. The sampling technique chosen was purposive sampling. The sample size was 20 children, consisting of 12 boys and 8 girls. The research subjects were children aged 5-6 years at Adinda Kindergarten. The data obtained were analyzed using a T-test. The results obtained based on the T-test calculation showed that where 4.72 1.729, thus was accepted and was rejected. Therefore, it can be concluded that there is an effect of the experimental method on science process skills in children aged 5-6 years at Adinda Kindergarten. This proves that children possess scientific process skills such as observing, classifying, conducting simple experiments, comparing, measuring, and communicating. Children construct knowledge through real-world experiences.